Eczema herpeticum: Kaposi’s varicelliform eruption - Vietti, Teresa; Çoruh, Mithat (The Turkish Journal of Pediatrics, 1961)
The history, physical findings and hospital course of three patients with eczema herpeticum are reviewed. In two of the patients the disease was iatrogenic in that the disease was contracted in the hospital from the third patient. Individuals with herpes simplex infection should avoid contact with patients who have extensive skin disease, especially if they are young infants.